2017
DOI: 10.1182/blood-2017-07-795658
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of BMP6 worsens the phenotype of HJV-deficient mice and attenuates hepcidin levels reached after LPS challenge

Abstract: Lack of either bone morphogenetic protein 6 (BMP6) or the BMP coreceptor hemojuvelin (HJV) in mice leads to a similar phenotype with hepcidin insufficiency, hepatic iron loading, and extrahepatic iron accumulation in males. This is consistent with the current views that HJV is a coreceptor for BMP6 in hepatocytes. To determine whether BMP6 and HJV may also signal to hepcidin independently of each other, we intercrossed and mice and compared the phenotype of animals of the F2 progeny. Loss of Bmp6 further repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
(33 reference statements)
5
33
0
Order By: Relevance
“…BMP‐6 gene knockout mice would exhibit obvious Hepcidin deficiency, which would lead to the accumulation of retinal iron. It has been found that an increase in serum iron can improve oxidative stress markers in mouse photoreceptors and significantly increase the oxidative stress in retina (Latour et al, ). In hepatocyte cell lines, heparin can effectively inhibit hepcidin expression by inhibiting phosphorylation of the SMAD1/5/8 proteins induced by BMPs (Poli, Asperti, Ruzzenenti, Naggi, & Arosio, ).…”
Section: Discussionmentioning
confidence: 99%
“…BMP‐6 gene knockout mice would exhibit obvious Hepcidin deficiency, which would lead to the accumulation of retinal iron. It has been found that an increase in serum iron can improve oxidative stress markers in mouse photoreceptors and significantly increase the oxidative stress in retina (Latour et al, ). In hepatocyte cell lines, heparin can effectively inhibit hepcidin expression by inhibiting phosphorylation of the SMAD1/5/8 proteins induced by BMPs (Poli, Asperti, Ruzzenenti, Naggi, & Arosio, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, erythropoietin retains the ability to suppress hepcidin in Bmp6 −/− mice . In a similar vein, inflammation induces SMAD1/5/8 phosphorylation in hepatocytes, but retains the ability to stimulate hepcidin in Bmp6 −/− mice . These data also suggest the possibility that erythropoietic drive and/or inflammation may also regulate the production of or response to another BMP family ligand to control hepcidin production.…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocytes, it has been well‐documented that inflammation induces hepcidin gene expression via the interleukin‐6 (IL‐6)/signal transducer and activator of transcription 3 (STAT3) pathway, via iron sensing through the transferrin receptor 2 (TfR2)/human hemochromatosis protein (HFE), and the bone morphogenetic protein (BMP)/hemojuvelin (HJV)/SMAD (a small mothers of decapentaplegic protein) pathways, and downregulated by erythroferrone (ERFE) ‐dependent and ‐independent mechanisms . Recent studies have also demonstrated that hepcidin expression can be upregulated by progesterone and mifepristone, two steroid hormones, through cell surface protein progesterone receptor membrane component‐1, transforming growth factor β1, SMAD1/5/8‐independent signaling by activin B, oxidases such as NADPH‐dependent oxidase 4 or artificially overexpressed urate oxidase (UOX), IL‐1β via inducing CCAAT enhancer‐binding protein δ (C/EBPδ) expression, peroxiredoxin‐2 which is a supporter for STAT3 transcriptional activity, fibroblast growth factor‐encoding gene, and downregulated by the immunophilin FKBP12 (FK506‐binding protein 1A) via binding with BMP type I receptor ALK2, cystathionine β‐synthase, TfR1, and matriptase‐2 …”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 99%